1992
DOI: 10.1159/000292724
|View full text |Cite
|
Sign up to set email alerts
|

Natural Killer Cell Activity in Patients with Gynecologic Malignancies: Correlation with Histologic Grading and Stage of Disease

Abstract: Basal natural killer (NK) cell activity in peripheral blood lymphocytes (PBLs) of 29 patients with gynecologic malignancy and 10 healthy controls was performed using K 562 cell line. A significant decrease of NK cell activity was observed in patients with gynecologic malignancy (p = 0.003). The NK cell activity of patients with poorly differentiated tumor or with stage IV of disease was significantly reduced with respect to patients at any other lower grade or earlier stage. We conclude that in patients with g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

1994
1994
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 6 publications
(8 reference statements)
2
2
0
Order By: Relevance
“…The decrease of natural killer activity was more important in presence of myometrial invasion > 50%, suggesting a relationship between basal immune reactivity and neoplastic progression. The results are in agreement with previous studies on gynecologic malignancies, which showed an immune reactivity decrease in advanced stage disease (14,15,17); however, in endometrial carcinoma the impairment of natural cytotoxicity was significant also in stage I disease, when the immune function is usually still preserved. The role of immune surveillance seems to be of primary importance also in the earlier phases of endometrial cancer growth, suggesting that natural killer activity is an effective functional index of immune status.…”
Section: Discussionsupporting
confidence: 92%
“…The decrease of natural killer activity was more important in presence of myometrial invasion > 50%, suggesting a relationship between basal immune reactivity and neoplastic progression. The results are in agreement with previous studies on gynecologic malignancies, which showed an immune reactivity decrease in advanced stage disease (14,15,17); however, in endometrial carcinoma the impairment of natural cytotoxicity was significant also in stage I disease, when the immune function is usually still preserved. The role of immune surveillance seems to be of primary importance also in the earlier phases of endometrial cancer growth, suggesting that natural killer activity is an effective functional index of immune status.…”
Section: Discussionsupporting
confidence: 92%
“…There have been studies in patients with cancer which demonstrate a link between overall survival and improved immunomodulators [1012]. Our data show that the average CD4, CD8 and NK cell levels were higher at almost every course of chemotherapy (Fig.…”
Section: Discussionsupporting
confidence: 54%
“…For example, cytotoxic immune response by T cells (including CD 4 and CD 8 ), as well as NK cells plays a key role in the recognition and destruction of malignant cells, and have been reported to be improved following massage therapy. NK cell cytotoxic activity is decreased in multiple advanced cancers, including gynecologic malignancies [10]. An increase in NK cells was shown to have a beneficial impact on survival in malignant melanoma patients [11].…”
Section: Introductionmentioning
confidence: 99%
“…The immune system is considered greatly important in the defence against neoplastic development (8)(9)(10)(11)(12)(13), and lymph nodes are fundamental components of the peripheral immune system. Beyond their role as a passive filter, lymph nodes play an active part in immunological defence and perform a barrier function during the spread of malignant neoplasia (14).…”
Section: Submitted 15 Novetiibrr 1994 a C W P T E D 21) Fdwuarj 1995mentioning
confidence: 99%